2015
DOI: 10.1111/jomf.12181
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents' Perceptions of Family Belonging in Stepfamilies

Abstract: Prior research has established that adolescents’ perceptions of family belonging are associated with a range of well-being indicators and that adolescents in stepfamilies report lower levels of family belonging than adolescents in two-biological-parent families. Yet, we know little regarding what factors are associated with adolescents’ perceptions of family belonging in stepfamilies. Guided by family systems theory, the authors addressed this issue by using nationally representative data (Add Health) to exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
84
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(95 citation statements)
references
References 43 publications
9
84
0
2
Order By: Relevance
“…This scale has been used previously by family scholars examining family belonging (King, Boyd, & Thorsen, 2015; King & Boyd, 2016). Early analyses examining the associations between family belonging and union formation and stability suggested that these associations were non-linear; differences were greatest comparing those with particularly low levels of family belonging to others, when treating this variable as a continuous measure the incremental effects across the range of family belonging were not clear.…”
Section: Methodsmentioning
confidence: 99%
“…This scale has been used previously by family scholars examining family belonging (King, Boyd, & Thorsen, 2015; King & Boyd, 2016). Early analyses examining the associations between family belonging and union formation and stability suggested that these associations were non-linear; differences were greatest comparing those with particularly low levels of family belonging to others, when treating this variable as a continuous measure the incremental effects across the range of family belonging were not clear.…”
Section: Methodsmentioning
confidence: 99%
“…Although the quality of an individual's relationships with each family member undoubtedly influences perceptions of family belonging, feelings of belonging are conceptually distinct from these dyadic relationships. Empirical evidence supports this distinction (King, Boyd, & Thorsen, ).…”
Section: Introductionmentioning
confidence: 92%
“…In any case, our results demonstrate the leading role fathers take in their stepfamily when doing family and thus provide a tentative indication that not only mothers should be seen as responsible for establishing and maintaining family relationships in stepfamilies (King, Boyd, & Thorsen, 2015). As our results suggest, fathers in stepfamilies also assume the role of mediator and interpreter, indicating that parents' central position in the stepfamily should be considered a characteristic of the role of the biological parent in a stepfamily, rather than a sole artifact of the cultural ideology of the motherhood myth (King, Boyd, & Thorsen, 2015;Weaver & Coleman, 2010). However, these conclusions are tentative given that they depend on solely two qualitative studies that focused on the perspective of biological parents in stepfamilies.…”
Section: Discussionmentioning
confidence: 53%
“…Despite extensive coverage of research on the experiences of stepparents and stepchildren, only a few studies have explicitly investigated the experiences of resident biological parents (Weaver & Coleman, 2010). However, both quantitative research based on a nationally representative sample of adolescents in stepfather families within the United States (King, Amato, & Lindstrom, 2015;King, Boyd, & Thorsen, 2015;King et al, 2014) and qualitative research (Pylyser et al, 2018) have suggested that biological parents are key to the formation and development of stepfamily relationships and closeness, given their connecting role as parent and partner in the stepfamily.…”
Section: The Biological Parent In Stepfamiliesmentioning
confidence: 99%